2019
DOI: 10.1590/0034-7167-2018-0551
|View full text |Cite
|
Sign up to set email alerts
|

Lawsuits in health: an integrative review

Abstract: Objective: To analyze the national and international scientific evidence available in the literature on types of judicialization of health lawsuits. Method: Integrative review, which selected primary studies in the PubMed, LILACS, Web of Science and Scopus databases, with the Descriptors: judicial decisions, health's judicialization, Saúde (in Portuguese), Health, and the keyword: Judicial Action. Results: 30 studies were selected. In Brazil, the majority were legal claims for medicines and the other for medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Em termos práticos, se o dinheiro é insuficiente para arcar com os planejamentos previstos e lidar com as demandas judiciais, automaticamente o contexto exige sua limitação, uma vez que o direito a saúde, que é coletivo, deve ser resguardado (9). Quanto à caracterização, a natureza predominante das ações judiciais é por medicamentos (12,(17)(18)(19)(21)(22)(23)(25)(26)(27)(28). Outros prevalentes incluem vagas de UTI (3,(25)(26)(27), cirurgias (12,, consultas e exames (3,10,12,17,26,27), alimentos e insumos (3,12,17,23,26,28) e tratamentos (9,17,22,25).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em termos práticos, se o dinheiro é insuficiente para arcar com os planejamentos previstos e lidar com as demandas judiciais, automaticamente o contexto exige sua limitação, uma vez que o direito a saúde, que é coletivo, deve ser resguardado (9). Quanto à caracterização, a natureza predominante das ações judiciais é por medicamentos (12,(17)(18)(19)(21)(22)(23)(25)(26)(27)(28). Outros prevalentes incluem vagas de UTI (3,(25)(26)(27), cirurgias (12,, consultas e exames (3,10,12,17,26,27), alimentos e insumos (3,12,17,23,26,28) e tratamentos (9,17,22,25).…”
Section: Discussionunclassified
“…Quanto à caracterização, a natureza predominante das ações judiciais é por medicamentos (12,(17)(18)(19)(21)(22)(23)(25)(26)(27)(28). Outros prevalentes incluem vagas de UTI (3,(25)(26)(27), cirurgias (12,, consultas e exames (3,10,12,17,26,27), alimentos e insumos (3,12,17,23,26,28) e tratamentos (9,17,22,25). Considerando a prevalência dos fármacos, dois estudos (21,26) demonstraram que em torno de 25 a 30% do total de medicações solicitados judicialmente incluem aqueles contidos nas listas oficiais do Sistema Único de Saúde.…”
Section: Discussionunclassified
“…A recent literature review analyzed 30 primary studies and confirmed that the process of judicialization due to malpractice occurs more frequently in the context of the use of medications, and, after that, other care processes were also the focus of the studies analyzed, especially the surgical procedure (7) . Regarding malpractices occurring during the perioperative period, nursing has a relevant role in the prevention of incidents.…”
Section: Introductionmentioning
confidence: 94%
“…Dentre os trabalhos encontrados, foram requeridos medicamentos como Adalimumabe e Etanercepte, indicados para tratamento de artrite reumatoide. Destaca-se que fazem parte da Relação Nacional de Medicamentos Essenciais (RENAME), todavia a população vem encontrando dificuldades no acesso, na qual a política de assistência farmacêutica apresenta falhas na logística da aquisição e distribuição dos fármacos (BATISTELLA et al, 2019). Santos et al (2018) destacam, em estudo com usuários diagnosticados com Diabetes Mellitus, que estes conhecem pouco sobre os direitos em saúde, embora os utilizem.…”
Section: Humanas E Sociaisunclassified